2004
DOI: 10.1021/ma049218m
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide Pseudorotaxanes, Rotaxanes, and Catenanes Based on Bis(5-carboxy-1,3-phenylene)-(3x+2)-crown-x Ethers

Abstract: We previously reported that the polyamide 3a derived from bis(5-carboxy-1,3-phenylene)-32-crown-10 (BCP32C10, 1a) and 4,4‘-oxydianiline (ODA, 2) was completely insoluble and attributed this to the formation of mechanical cross-links via self-threading of the crown ether moieties by the amide backbone through hydrogen bonding. Moreover, polycondensation of 1a with bis[4-(m-aminophenoxy)phenyl]phenylphosphine oxide (m-BAPPO, 4) produced polyaramide 5a that, like its analogue 3a, was insoluble in all solvents exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 76 publications
2
35
0
2
Order By: Relevance
“…On the basis of this, Gibson et al 22 indicated the possible formation of polyrotaxanes, catenanes, and polycatenanes due to cyclization in the polymerization reaction. The highmembered ring cycles can first form branched polyamides that can finally progress to networks because of crosslinked catenate species.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of this, Gibson et al 22 indicated the possible formation of polyrotaxanes, catenanes, and polycatenanes due to cyclization in the polymerization reaction. The highmembered ring cycles can first form branched polyamides that can finally progress to networks because of crosslinked catenate species.…”
Section: Resultsmentioning
confidence: 99%
“…(5) Threading of cycles on linear polymers (pseudorotaxanes) and the formation of catenanes may take place as suggested by the experiments of Gibson and coworkers. [42] In summary, it may be concluded that self-dilution (plus self-acceleration) more or less compensates or overcompensates the reduction of Ct resulting from increasing chain length. At this point it should be mentioned that this conclusion is also relevant for the proper understanding of Equation (2).…”
Section: H R Kricheldorfmentioning
confidence: 96%
“…Recently, a new class of polyaramides has been synthesized by Gibson et al that contain the crown ether motif in the repeat unit [16]. The class is synthesized using a step growth reaction with a given bis(5-carboxy-1,3-phenylene)crown ether (BCP) and a diamine.…”
Section: Main Chain Rotaxanes Based On Polymeric Crowns (Including Crmentioning
confidence: 99%